A Decision-Theoretic Model of Behavior Change - Matsumori, Kaosu; Iijima, Kazuki; Koike, Yasuharu; Matsumoto, Kenji (Frontiers in Psychology, 2019)
Undesirable habitual or addictive behaviors are often difficult to change. The issue of “behavior change” has long been studied in various research fields. Several models for behavior change have converged to the hypothesis that attitudes, norms, and self-efficacy are important determinants of intentions and behavior. To improve the accuracy of behavior-change models, some researchers have tried to combine behavioral economics models with existing models for behavior change. However, these attempts have failed because the existing models [e.g., Theory of Planned Behavior (TPB)] are not consistent with Expected Utility Theory (EUT), which underlies various behavioral economics models. In the present paper, we clarify the corresponding components between existing models for behavior change and EUT, and propose a new model, the Decision-Theoretic Model of behavior change (DTM), which is a natural extension of ordinary EUT.